Vitamin E and Vitamin C Intake Among Lactating Mothers In Jakarta - Sheira Taflah Putri Handana; Diyah Eka Andayani; Ninik Mudjihartini (World Nutrition Journal, 2019)
Background and ObjectivesVitamin E is a lipid soluble vitamin which obtain only through diet. Vitamin E has many functions including antioxidant and well known to prevent lipid peroxidation in membrane cell. Vitamin C helps to regenerate vitamin E back into non radical. Vitamin E and C intake among vulnerable group such as lactating mother still uncleared especially in Jakarta. The aim of this study to determine level of vitamin E and C intake among lactating mothers in JakartaMethods60 lactating mothers aged 20–40 years old in 1–6 months postpartum were recruited on Grogol Petamburan and Cilincing Public Health Centre in Jakarta. This cross sectional study held from March 2019 until April 2019. Vitamin E and C dietary intake were collected with semi quantitative food frequency questionnaire. Descriptive analysis was used in this study.ResultsThis study showed that median value  of vitamin E intake was 6.50 (1.20-43.10) gram/day with 91.7% subjects does not meet vitamin E recommended daily intake (RDA) recommendation (19 gram/day), otherwise 70% vitamin C intake was above RDA recommendation (100 gram/day) with median value is 120.05 (23.0-479.2) gram/day.ConclusionVitamin E intake among lactating mothers in Jakarta was not adequate and far below RDA recommendation but vitamin C intake among lactating mothers in Jakarta was adequate and met RDA recommendation.